Bucket working bodies with conveyor bottom: systematics and design features - Yu. M. Lyashenko; E. A. Revyakina; A. Yu. Lyashenko (Advanced Engineering Research, 2020)
Introduction. The creation of new types of bucket working bodies of excavators through synthesizing technical solutions to improve the transporting functions of the bottom is considered. These solutions are based on reducing the resistance and energy consumption under digging-in and scooping due to the transition from sliding friction to rolling friction during the movement of the rock mass along the bottom of the bucket.Materials and Methods. Analysis of the bulk materials handling processes using existing loading appliances identified design flaws that affect the efficiency of their operation. Advanced design diagrams of loading bodies were searched on the basis of the accumulated experience and the study of the morphological features of the existing equipment. Combinatorial analysis of possible combinations of elements with their various qualitative compositions, mutual arrangement, imposed links, and synthesis of new technical solutions for loading and transportation modules are carried out. Results. The results of the morphological synthesis implementation were the systematization and development of designs of bucket working bodies with a bottom in the form of a roller surface and a closed belt, as well as with a conveyor-type drive mechanism. The application of rollers as a supporting surface of a loaded rock mass causes a decrease in friction forces and in the power capacity of the work process. In addition, rotating rollers provide uniform abrasion of the working surface, which increases significantly the time to the equipment breakdown and increases the process efficiency. Working bodies with a drive mechanism make it possible to activate the interaction of the conveyor bottom in the form of a closed belt with the rock mass and, as a result, to accelerate the process of filling the bucket container.Discussion and Conclusions. The bucket working bodies described in the paper compare favorably with existing analogues in that they provide a reduction in the time to digging-in, scooping and unloading, a decrease in specific energy consumption, an increase in bucket filling, which ultimately contributes to an increase in productivity. A slight increase in the structural complexity and cost of the working body causes additional capital costs, which are paid back within two to four months.